Generation of optical frequency combs using a photonic crystal cavity. Issue 1 (1st February 2019) - Francis, Henry; Chen, Si; Ho, Chi‐Hua; Che, Kai‐Jun; Wang, Yun‐Ran; Hopkinson, Mark; Jin, Chao‐Yuan
Abstract : Using cascaded intensity and phase modulators to achieve frequency combs is a common technique. However, this technique has not yet been employed to achieve optical frequency combs (OFCs) at the nanoscale. A theoretical model based on temporal coupled mode theory is developed to simulate an all‐optical photonic crystal modulator. The concepts used to generate an OFC based on electro‐optic modulators are then extended to the nanophotonic domain. It is theoretically proven that an OFC can be generated via all optical modulation of nanophotonic devices.